Differences of Salat Time Recording: Analytical Contemporary Method of Kitab al-Khulashah al-Wafiyyah - Ahmad Fadholi (Justicia Islamica, 2022)
The discussion on calculating Islamic prayer (salat) times contained in the Kitab Khulashah has its characteristics. The calculation process of salat beginning times has referred to the triangular ball algorithm system. Besides, there are also daqoiqut tamkin corrections presented through tables and calculator calculation methods. This interesting calculation can be studied; how the transformation system of salat time coordinates and the accuracy level of the salat beginning times calculation results. This study uses a library research paradigm with a qualitative theory verification approach using an arithmetic approach, and the results are presented descriptively and then compared with similar methods. The results show that the coordinate transformation refers to the modern astronomical system, and the calculation system has used spherical trigonometry (spherical triangle). The calculation results differ from 0 to 3 minutes with contemporary methods. Differences in data and methods cause it. Suppose the calculation is using the contemporary method. In that case, there is a difference of 0 seconds to 12 seconds. This indicates that modifications to the contemporary calculation system will produce a more accurate calculation when the calculation is made.